Proteomic response of mouse pituitary gland under heat stress revealed active regulation of stress responsive proteins. (October 2016) - Memon, Shahar Bano; Lian, Li; Gadahi, Javaid Ali; Genlin, Wang
Abstract: The mapping of tissue proteomes can identify the molecular regulators and effectors of their physiological activity. However, proteomic response of a mammalian tissue against heat stress (HS) particularly of the pituitary gland has not yet been resolved. The proteomic response of the mouse pituitary gland against HS at 40 o C was evaluated by iTRAQ. We found that, HS actively regulates stress-related proteins. Among 375 differentially expressed proteins, 26 up and 46 downregulated proteins were found as stress responsive proteins. Two proteins belonging to the HSP70 and one to HSP90 family were found upregulated. Meanwhile, the expression of HSP90α (Cytosolic), HSP60, and HSP84b were observed to be downregulated. A neuroprotective enzyme Nmnat3 was observed to be significantly upregulated. Three proteins related to the intermediate filament (IF) proteins (lamins, vimentin and keratins) were also found to be upregulated. We reported, an association between the IF proteins and HSPs as a biological marker of HS. The expression of Apo A-IV was upregulated and might be one explanation for low food intake during HS. Our findings indicated that, differentially expressed proteins might be played important roles in combating HS. Graphical abstract: Highlights: HS actively regulates stress-related proteins. A total of 375 differentially expressed proteins were identified. A neuroprotective enzyme Nmnat3 was observed to be significantly upregulated. Three intermediate filament proteins were also found to be upregulated. We reported, an association of IF proteins and HSPs as a biological marker of HS.